The relationship between buoyancy and airborne weight in synchronized swimmers - Homma, W. (Japanese Journal of Sciences in Swimming and Water Exercise, 2017)
The purpose of this study was to examine the relationship between the buoyancy of synchronized swimmers and the airborne weight of basic positions. Whole-body volume, buoyancy, underwater weight, and airborne weight at 12 levels in basic positions were measured for eight female synchronized swimmers (15.6 ± 2.98 years, 1.60 ± 0.05 m, 52.7 ± 4.40 kg). The main results were as follows. The surplus buoyancy of synchronized swimmers was 2.19 ± 1.78 kgf. In the upright position, the airborne weight of double arm changed from 8.58 ± 0.63 kgf (16.3%) at the shoulders to 28.44 ± 2.99 kgf (53.9%) at the mid-pelvis. In the inverted position, the airborne weight of double leg changed from 3.77 ± 0.97 kgf (7.1%) at the kneecap to 7.77 ± 0.95 kgf (14.7%) at the clotch level. In the horizontal position, the airborne weight for the ballet leg double changed from 7.18 ± 0.94 kgf (13.6%) at the mid-thigh to 12.95 ± 1.72 kgf (24.6%) at the crotch level. Although there was no effect from greater surplus buoyancy on positions with a large airborne weight, swimmers with greater buoyancy could more efficiently hold parts of the body above the water in positions with a small airborne weight. It is important to increase supporting force via propulsive techniques to support large airborne weights.